Ameliorative Effect of Carob Pods Extract (Ceratonia siliqua L.) against Cyclophosphamide Induced Alterations in Bone Marrow and Spleen of Rats - Sawsan Ahmed Abd Elhalim, Hayat Mohamed Sharada, Ibrahim Abulyazid, Wael Mahmoud Aboulthana, Sohaila Talaat Abd Elhalim (Journal of Applied Pharmaceutical Science, 2017)
Cyclophosphamide (CYP) belongs to the anticancer drugs that exhibit potentially life-threatening effects on the immune and hematopoietic systems. The study aimed to assess efficiency of carob pods extract against the adverse CYP effect on spleen and lymphatic tissues which are the most sensitive components of immune system. In the present study, the hematological indices and markers of oxidative stress were assessed. In addition, the native protein, lipoprotein patterns, calcium moiety of native protein, catalase (CAT), peroxidase (GPx), α- and β- esterase (EST) isoenzymes and genomic DNA patterns were electrophoretically detected in both of bone marrow and spleen tissues. It was verified that CYP caused significant (P
Keywords: Cyclophosphamide, Bone marrow, Spleen, Ceratonia siliqua, Electrophoresis, Isoenzymes.